Notions of border in regionalism theory and praxis: A critical overview - Souza, Gustavo Matiuzzi de (Civitas: revista de Ciências Sociais, 2018)
This article provides a concise and critical overview of the notions of border within regionalism theory and praxis. It also discusses the last decade’s increase of border barriers in this globalized world and its relation to regionalism. We provide a historical approach to theoretical construction and consider implied ideas of border derived from theoretical and empirical developments of regionalism. This paper finds that old regionalism indicates a notion of border as separation; new regionalism implies a notion of border as filter. The current wave of comparative regionalism identifies two apparently contradictory processes (multilevel regionalisms and nationalisms) that actuate the formation of (cross) border regions embedded into tangled webs of global networks, which requires a globalist perspective of regionalist dynamics. ***Noções de fronteira na teoria e práxis do regionalismo: Uma visão crítica*** Este artigo fornece um panorama conciso das noções de fronteira na teoria e nas práxis do regionalismo. Também se discute o aumento, na última década, das barreiras fronteiriças neste mundo globalizado e a sua relação com o regionalismo. Através de uma aproximação histórica à construção de teorias, considera-se as ideias implícitas de fronteira derivadas dos desenvolvimentos teóricos e empíricos do regionalismo. Este paper conclui que o antigo regionalismo indica uma noção de fronteira como separação. O novo regionalismo implica em uma noção de fronteira como filtro. A atual onda do regionalismo comparado identifica dois processos aparentemente contraditórios (regionalismo multinível e nacionalismo) que acionam a formação de regiões (trans)fronteiriças incorporadas em teias entrelaçadas de redes globais, exigindo uma perspectiva globalista no estudo dessas dinâmicas.